Age and Seasonal Aspects of Sexual Differences in Social Vole, Microtus socialis, (Rodentia, Arvicolinae), in the South of Ukraine - Sinyavskaya, I.A. (Вестник зоологии, 2013)
Expression of sexual differences in social vole populations of virgin steppe reserve “Askania Nova” analyzed in the article. It is established that the severity of the sexual differences of value morphological features depending on the age of the animals and to a lesser degree on the season.